Increased level of presepsin in patients with acutely decompensated cirrhosis predicts development of acute-on-chronic liver failure. (March 2023) - Zanetto, A.; Mion, M.M.; Ferrarese, A.; Shalaby, S.; Germani, G.; Gambato, M.; Russo, F.P.; Farinati, F.; Basso, D.; Burra, P.; Senzolo, M.
Abstract : Introduction: The clinical course of acutely decompensated cirrhosis (AD) is heterogeneous. Presepsin (PSP) is a soluble CD14-subtype biomarker that reflects Toll-like receptor activity as the immune response to endotoxaemia and bacterial infections, and it has regulatory properties of the adaptive immune system. Aim: We conducted a prospective study to assess whether, in hospitalized patients with AD, plasmatic PSP could predict development of ACLF. Material and Methods: AD patients were recruited at admission and underwent determination of PSP (chemiluminescent immunoassay). All patients were followed for 1 year, and predictors of ACLF were assessed by Cox analysis. Results: 99 AD patients were included (median age: 61 years; 65% had alcohol-related cirrhosis). The main reasons for AD were infections and alcoholic hepatitis (52% and 22%, respectively). Median MELD and CLIF-C AD scores were 18 and 54, respectively. Median PCP was 674 U/L (308-1700). Thirty-six patients developed ACLF. PSP was higher in patients who experienced ACLF vs those who did not (1253 [670-2562] vs 375 [245-722], respectively; p<0.0001). Among patients who didn't develop ACLF, PSP was comparable between those who were re-hospitalized due to cirrhosis complications and those who were not re-hospitalized (432 vs 355, respectively). Cox analysis demonstrated that PSP was independently associated with ACLF (Table). PSP AUROC was good and comparable to CLIF-C AD score (0.78 vs 0.79, respectively). A PSP value > 660 had 77% sensitivity and 70% specificity for the development of ACLF. In a sub-analysis including patients at lower risk of ACLF (i.e. CLIF-C AD score ≤50 and Child B), PSP was significantly higher in those who developed ACLF than in those who did not (1054 vs 250, respectively). Conclusion: PSP can be a useful, single and independent biomarker to identify trajectories of AD, even in patients at lower risk of ACLF, if this is confirmed in larger cohorts.